AYAT-AYAT TERKAIT LEMBAGA NEGARA DALAM PERSPEKTIF AL-QUR’AN - Muhamad Ginanjar; Muhammad Fawwaz Zikrillah; Muhammad Nabil Hibatullah (Melati Institute, 2023)
Discussing Religion and State seems to never end. This study aims to examine more deeply the concept of state institutions using the maudhu'i interpretation approach. This study uses a qualitative method of literature study which refers to scientific works, articles and literature. The results of the study show that the state is a solid building which includes all rules related to social governance. While state institutions are state organs that function to complement a state in order to create the goals of the state. In the Qur'an there are several terms regarding the State including al-Balad, balad, bilad, qoryah, baldah, and ad-dar. Religion contributes to achieving the goals of state institutions, the function of religion here is to be in line with what is the source of society.